Pelabuhan Udara Paal Merah Dalam Agresi Militer Belanda Di Jambi tahun 1947-1950 - Wahyu Zamzami; Nelly Indrayani (Prodi Ilmu Sejarah, Jurusan Sejarah, Seni dan Arkeologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Jambi, bekerja sama dengan Masyarakat Sejarawan Indonesia, Jambi, 2021)
The existence of air transportation cannot be separated from human life that supports politics and defense and security. The Paal Merah Jambi airport has been around since 1933 and is a symbol of the transportation revolution of the Jambi area. Dutch military aggression I and II helped drag Paal Merah into conflict by using it as one of the entrances to control Jambi and as an important transportation asset. On the other hand, during military aggression the Jambi government had planned to build an airline but failed. This study aims to determine the history and role of the Paal Merah Jambi airport during the Dutch military aggression. The research method used in this research is historical methods, consisting of heuristics, source criticism, interpretation and historiography. Through this method, it shows that the construction of Paal Merah Jambi airport is influenced by the need for efficient transportation for communication and defense. However, over time it has begun to penetrate the economic sector through commercial flights. The construction of the Paal Merah Jambi airport is indeed influenced by economic, social and political backgrounds. In its historical development, Paal Merah Jambi airport is an important aircraft transit place for domestic and international flights. In addition, this place also provides aircraft refueling, which is no longer found.